2021 IEEE International Conference on Image Processing (ICIP) 2021
DOI: 10.1109/icip42928.2021.9506494
|View full text |Cite
|
Sign up to set email alerts
|

3d Autoencoders For Feature Extraction In X-Ray Tomography

Abstract: Real-time steering of time-resolved or in-situ X-ray tomography requires capturing changes in morphological descriptors in a sample (e.g., porosity, particle size, and crack width) during continuous data acquisition. Segmentation of 2D or 3D images followed by quantitative measurement is the conventional method for tracking changes in these descriptors with respect to a previous time-step or a 3D search in a volume. However, image segmentation is expensive. As a faster and unsupervised alternative, we propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…With the automatic lens changing mechanism we can easily pad high resolution with low resolution projections and correct the high-resolution scans from local tomography artifacts (Xiao et al, 2007). Finally, we plan to add AI-based methods (Schoonhoven et al, 2020;Tekawade et al, 2021) for detecting events and trigger data saving automatically. In fast-evolving dynamic systems, automatic segmentation, classification, and detection may allow for steering tomographic experiments, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…With the automatic lens changing mechanism we can easily pad high resolution with low resolution projections and correct the high-resolution scans from local tomography artifacts (Xiao et al, 2007). Finally, we plan to add AI-based methods (Schoonhoven et al, 2020;Tekawade et al, 2021) for detecting events and trigger data saving automatically. In fast-evolving dynamic systems, automatic segmentation, classification, and detection may allow for steering tomographic experiments, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious and historically primary application of X-rays is medicine. There are many works here that use autoencoders to look for anomalies in X-ray images, e.g., [ 46 , 47 , 48 ].…”
Section: Related Workmentioning
confidence: 99%
“…In previous work, the authors from ANL showed that if U-net is too deep, it overfits on the shapes observed in the training data, leading to models that do not generalize accurately [1]. Further details about the training and data sampling algorithm were detailed previously [9].…”
Section: Surface Determinationmentioning
confidence: 99%
“…Each subset was reconstructed using DeepRecon as well as a traditional Feldkamp-Davis-Kress (FDK) reconstruction algorithm. Both datasets were then directly segmented (or binarized) using the surface determination algorithm from TomoEncoders, which utilizes 3D fully convolutional 1 More info about this article: http://www.ndt.net/?id=26583 https://doi.org/10.58286/26583 11th Conference on Industrial Computed Tomography, Wels, Austria (iCT 2022), www.ict-conference.com/2022 neural networks (fCNN) to perform surface segmentation [5], resulting in a binarized volume which implicitly determines the surface. For segmentation, the labeled mask for the training and testing data (two separate specimens) was generated from the full exposure data.…”
Section: Introductionmentioning
confidence: 99%